Haven between tides an integration of dreamscapes and biophilic design for the enhancement of the culture of mangrove conservation in San Juan, Batangas - Adlawan, Nicole Anne Marie C. (College of Architecture, University of the Philippines Diliman, 2019)
As a coastal country, the Philippines depends on marine resources such as the mangrove species. However, human exploitation of these resources led to the reduction of the coverage of mangroves. Although there have been rehabilitation and conservation projects, the degradation of the mangrove species continued. Due to this, this thesis aims to solve the problem on mangrove degradation through nurturing the relationship between the youth and nature by integrating dreamscapes and biophilic design to a waterfront development in Barangay Nagsaulay, San Juan, Batangas. Interviews and household surveys showed that there is still a lack of involvement with mangrove conservation projects and awareness despite having a culture of mangrove conservation. By integrating the Seven Environmental Principles of Nature to the different functions of the mangrove ecosystem, the development will serve as an avenue for cultivating environmentalism in the youth. The proposed landscape design "Mangrove Harbour" aims to groom environmentalists at a young age and educate the visitors, both locals and tourists, through interactive imagery and outdoor play